Pelayanan Administrasi di Bagian Tata Usaha Sekolah Menengah Atas Negeri 1 Batusangkar Kabupaten Tanah Datar - Fadhlan, Fadhlan (LPPM Universitas Ekasakti, 2023)
The study aims to determine Administrative Services in the Administration Section of Senior High School 1 Batusangkar, Tanah Datar Regency, obstacles in services, and Efforts made in Administrative Services in the Administration Section of Senior High School 1 Batusangkar. The type of research used in writing this thesis is qualitative with a descriptive approach. This study describes everything related to administrative services in the administration of Senior High School 1 Batusangkar. The data sources for this study are primary data and secondary data. The study subjects were the principal, head of school administration, teachers, dapodik operators, guardians, and students using the purposive sampling technique, namely determining informants based on certain considerations. The data collection technique for this study uses observation, interviews, and documentation. The results of this study indicate that services in the administration section of Senior High School 1 Batusangkar have not been implemented properly; the obstacles seen in the administrative service system at Senior High School 1 Batusangkar include inadequate facilities and infrastructure in administrative services and the lack of employees who have an educational background in the field of administrative services. Efforts can be made to overcome these obstacles by preparing all administrative service needs well, including facilities, infrastructure, and staff. This is a special concern so that administrative services at SMA Negeri 1 Batusangkar can provide optimal service with satisfactory results for the community and co-workers.